Laparoscopic resection is not superior to endoscopic resection for relative small gastric gastrointestinal stromal tumors: A propensity score-matched study - Li, De-Liang; Zhou, Yang-Yang; Zhang, Ji-Yu; Liu, Dan; Zhao, Li-Xia; Liu, Bing-Rong (Frontiers in Oncology, 2022)
Background and Aim Endoscopic resection (ER) and laparoscopic resection (LAP) have been recommended for the treatment of gastric gastrointestinal stromal tumors (GISTs) less than 2 cm. However, the therapeutic approach for gastric GISTs between 2 and 5 cm in diameter is still under debate. In this retrospective study, we aimed to evaluate the feasibility, efficacy, and safety of ER for gastric GISTs (2–5 cm) compared with LAP. Methods From January, 2011 to January, 2018, 197 patients with GISTs at our institution with tumor diameter between 2 and 5 cm were included in our study. Clinical baseline characteristics, histopathological results, and perioperative outcomes were collected and compared in all the patients. Propensity score matching (PSM) methods were used to balance baseline characteristics. Results There was no significant difference in age (p = 0.246), gender (p = 0.572), tumor location (p = 0.333), pathological risk classification (p = 0.543), Ki-67 index (p = 0.212), and follow-up time (p = 0.831) in the ER and LAP groups. However, significance difference was found in times to liquid diet intake (4.45 ± 1.2 vs. 5.40 ± 1.5 days, p = 0.013) and hospital stays (7.72 ± 1.1 vs. 10.01 ± 1.3 days, p < 0.001). During the follow-up period, there was one recurrence in the ER group vs. two recurrences in the LAP group. After PSM, the tumor size was balanced between the two groups with 49 patients in each group. The times to liquid diet intake (4.18 ± 1.3 vs. 5.16 ± 1.6 days, p = 0.042) and hospital stay days (7.12 ± 1.1 vs. 9.94 ± 1.3, p < 0.0001) were still short in the ER group. Conclusions ER is more associated with a quick postoperative recovery than LAP. ER could be an alternative approach for gastric GISTs (2–5 cm). However, the long-term follow-up outcomes are still unclear and random control trials are needed.